Single Motherhood and (Un)Equal Educational Opportunities : Evidence for Germany - Philippe Mahler; Rainer Winkelmann (Institute for the Study of Labor (IZA), 2004)
We examine the effect of single motherhood on children's secondary school track choice using a sample of 14 years old children drawn from the German Socio-Economic Panel. In line with previous studies for the U.S., the U.K. and Sweden, we find a negative correlation between disrupted family structure and children's educational outcome. Looking for alternative explanations for this correlation, we use ordered probit regression models to control for factors related to single motherhood such as lower educational background, lower household income and higher labor supply of the mother. Our evidence suggests that single parenthood reduces school attainment mainly because it is associated with lower resources (income and time) available for the child.
Keywords: I21; J12; 330; school choice; educational attainment; ordered response model; German Socio-Economic Panel; Bildungsniveau; Alleinerziehende; Kinder; Bildungschancen; Schätzung; Deutschland